Case Report: A Highly Variable Clinical and Immunological Presentation of IKAROS Deficiency in a Single Family - Kuijpers, Taco W.; Tromp, Samantha A. M.; van Leeuwen, Ester M. M.; de Bree, Godelieve J. (Frontiers in Immunology, 2022)
Here we describe a novel mutation in the IKZF gene encoding IKAROS, as the cause of common variable immunodeficiency (CVID). The identification of the same defect in the IKZF gene with manifestations of asymptomatic selective IgA deficiency and chronic ITP in the father and her younger brother, respectively, demonstrates the large variability of this genetic defect in one single family, while living in the same environment with a relatively similar genetic background. As discussed, clinical penetrance of the molecular defects identified by mutations in IKZF and other common gene defects in CVID in familial immune-related abnormalities makes genetic testing a necessary step for diagnosis, management and counseling, as part of the routine immunological workup.